Effect of glutathione spray on the growth of three genotypes of Cucumis sativus L. affected by water stress - Abd, Aziz Mahdi; Mohammed, Hussien Aziz; AbdulHasan, Waleed Fouad (Journal of agricultural, environmental and veterinary sciences, 2020)
Experiment was conducted during spring season 2017 in the experimental station of the Department of Horticulture and Landscape, College of Agriculture Diyala University, Iraq. In order to understand some of the effects and adaptations of the vegetative growth of the cucumber plant affected by water stress and the experiments were arranged in a Split-Split Plot Design in R.C.B.D. and with three replicates. The experiment factors were as follows: the genotypes of cucumbers, namely Demmy (V1) and Ghazeer (V2) and Wesam (V3), and second: two levels of irrigation are Complete irrigation 100% (I1) of field capacity and 50% of complete irrigation (I2). Third, spray glutathione in three concentrations (0, 50, 100) mg L-1 and its symbol (G0, G1, G2). The results of the study showed the superiority of the genotype plants in the number of leaves and leafy area (91.72 leaves plan-1 and 213.9 dcm2 plants-1) respectively. whereas the irrigated plants exceeded the level 100% significantly for all studied traits compared with the level of irrigation 50%. Also, the glutathione spray levels exceeded 50 and 100 mg L-1 (without significant difference between them) by all the characteristics compared to the comparison treatment (G0). The results of the triple interference between the genotypes, irrigation levels, and levels of glutathione spraying showed significant differences in the vegetative growth of cucumber plants, Since the treatment of interference V3I1G2 was superior to the number of branches (5, 766 branches plant-1), the total paper area (239.0 dcm 2 plants-1) and the concentration of chlorophyll (45.72 spad), While treatment V3I1G1 was superior to the number of leaves (99.66 leaves per plant-1) and dry matter percentage in the vegetative total(16.00%), and treatment V2I1G2 to excellence in plant length (148.6 cm).
Keywords: glutathione; water stress; genotypes; chlorophyll